1990
DOI: 10.1136/jmg.27.4.252
|View full text |Cite
|
Sign up to set email alerts
|

Ellis-van creveld syndrome, Jeune syndrome, and renal-hepatic-pancreatic dysplasia: separate entities or disease spectrum?

Abstract: We describe two children with multiple abnormalities, neither of whom fits neatly into a classical diagnostic category, but who show overlapping features of Ellis-van Creveld syndrome, Jeune syndrome, and renal-hepatic-pancreatic dysplasia. It seems possible that these three entities form part of a disease spectrum rather than being distinct conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 6 publications
0
46
0
1
Order By: Relevance
“…These abnormalities are indistinguishable from those seen in the hepaticpancreato-renal syndrome (HPRS). Brueton et al [1990] reported two patients with overlapping clinical data of JATD and HPRS with hepatic involvement present since birth, although in JATD, it is seen in later years. Hunter et al [1974] described other patients with liver ®brosis associated to diverse abnormalities, such as certain facial characteristics that are present in our patients, but in addition, their patients had ocular colobomata and encephalopathy.…”
Section: Discussionmentioning
confidence: 92%
“…These abnormalities are indistinguishable from those seen in the hepaticpancreato-renal syndrome (HPRS). Brueton et al [1990] reported two patients with overlapping clinical data of JATD and HPRS with hepatic involvement present since birth, although in JATD, it is seen in later years. Hunter et al [1974] described other patients with liver ®brosis associated to diverse abnormalities, such as certain facial characteristics that are present in our patients, but in addition, their patients had ocular colobomata and encephalopathy.…”
Section: Discussionmentioning
confidence: 92%
“…Age of occurrence has been variable. JATD can also occasionally be associated with GI malformations including cystic changes of the pancreas with fibrosis, Hirschsprung's disease, and malrotation as a manifestation of the ciliopathy [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…10 Los pacientes que sobreviven pueden desarrollar falla renal progresiva, anomalías hepáticas, pancreáticas y retinales. 9,11 Los hallazgos radiológicos típicos incluyen los siguientes: 9 • Tórax estrecho, costillas cortas, horizontalizadas, clavículas altas, en manubrio.…”
Section: Introductionunclassified